2019
DOI: 10.15298/arthsel.28.2.03
|View full text |Cite
|
Sign up to set email alerts
|

New data on the millipede genus Altajosoma Gulička, 1972 from southwestern Siberia, Russia (Diplopoda: Chordeumatida: Diplomaragnidae) 

Abstract: Based on fresh and reexamined material from SW Siberia, the distributions of seven diplomaragnid millipede species have been supplemented, refined and updated. The following few taxonomic changes are proposed:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A new surge in the faunistic research of Myriapoda in Khakassia started when Nefediev reported two millipedes: a still undescribed julid species, Julus sp. 2 and a diplomaragnid, Altajosoma bakurovi (Shear, 1990) [Nefediev, 2019a]. At the same time, the first records of four geophilomorph centipede species, viz.…”
Section: Introductionmentioning
confidence: 97%
“…A new surge in the faunistic research of Myriapoda in Khakassia started when Nefediev reported two millipedes: a still undescribed julid species, Julus sp. 2 and a diplomaragnid, Altajosoma bakurovi (Shear, 1990) [Nefediev, 2019a]. At the same time, the first records of four geophilomorph centipede species, viz.…”
Section: Introductionmentioning
confidence: 97%